Las reformas tributarias del milenio y su relación con los ingresos tributarios y la pobreza (2018)
The citizens of a country must contribute to the tax burdens for the support of their state apparatus, including those expenses aimed at the community's welfare. In Colombia the Congress of the Republic has approved nine tax reforms so far in the millennium. However, this research did not take into account that of 2016, since being the most recent its results cannot be quantified. The changes introduced in the reforms have increased the tax revenues of the Central Sector, supported mainly by the collection of income tax and VAT and also supported by the income of the CREE and wealth, which have been gaining participation in recent years; however, this growth is not compatible with the dynamics presented by the national monetary poverty and national extreme poverty rates, which despite showing significant decreases during the period, their percentage variations differ from the behavior of the tax resources which is why they generate questions about the social purpose of the State.